Nigeria's Adoption of Robotic Lawyers: Legal and Socio-Economic Challenges - Paul Atagamen Aidonojie; Obi Eregbuonye; Adesoji Kolawole Adebayo; Shedrack Ekpa; Ketut Sukewati Lanang Putra Perbawa (BESTUUR, 2024)
Technological advancement has greatly enhanced the global environment, it has improved every facet of the global industry. Currently in Nigeria, the Legal Profession has taken a bold dive by incorporating the use of technology in enhancing the practice of law. However, the current innovation of robotic lawyers in most countries may seem to be consistent with their legal systems. In this regard, it suffices to opine that given the fact that Nigeria is a developing country, there are legal and socio-economic issues that may affect or truncate the adoption of a robotic lawyer in Nigeria. It is in this regard that this study adopted a hybrid method of research in ascertaining the relevance of robotic lawyers, and the legal and socio-economic issues. Questionnaires were distributed to 305 respondent residents in Nigeria. The study found that the current trend of robotic lawyers is quite impressive, however, the nomenclature of law concerning the study and practice of Law in Nigeria does not recognize a robotic lawyer. Furthermore, some socio-economic issues such as internet fraudster, unemployment, insecurity, and poor maintenance culture may pose a challenge to the adoption of a robotic lawyer in Nigeria. In this regard, it was therefore concluded and recommended that for a smooth adoption of robotic lawyers in Nigeria, there is a need for legal approval and streamlining their roles to mere advisory to a client, training of Nigerian lawyers and judges to enhance the legal profession.